Strategi Modernisasi Pemasaran UP2K Memalui Digital Marketing Di Desa Bangun Seranten Kecamatan Muara Tabir Kabupaten Tebo - Alam, Sandi; Zulkifli, Zulkifli; Syahwami, Syahwami; Albadry , Syah Amin; Nasir, Muhammad; Burhanuddin, Burhanuddin; Darmawan, Darmawan; Hasdani, Hasdani (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2024)
UP2K Product Marketing Strategy through the Implementation of Digital Marketing aims to help and determine the impact of digital marketing on UP2K product sales, by comparing UP2K which uses digital media as a means of promotion and product sales. with UP2K who have not used digital media as marketing, and to find out how to implement digital marketing. Marketing efforts to UP2K in Bangun Seranten Village, Muara Tabir District, Tebo Regency to increase sales volume and also increase profits for UP2K entrepreneurs.